PENERAPAN PRINSIP KEBIJAKAN ZERO DELTA Q DALAM PEMBANGUNAN WILAYAH - Indriatmoko, Robertus Haryoto (Center for Environmental Technology, 2010)
Principle of zero delta Q policy is that a development should notÃ‚Â increase water discharge to drainage system. Policy of zero delta Q is apply to zone of recharge area and other zone which is not recharge area as well, because this area which is not as recharge area has contribute a great deal to local flood. Based on this therefore implemention of policy of zero delta Q is applied to urban area such as Jakarta. Activities proposed for Jakarta were: 1. Optimize use of water reservoir, pond and site; 2. Implementation of artificial recharge or could be combined with biopore; 3. Effective land use by provide open green areas; and 4. Normalization of drainage system.Ã‚Â Keywords : policy, zero delta q, flood, artificial recharge, biopore, development